Histological Studies on the Oesophagus of Adult Guinea Pig (Cavia porcellus) - K.Raja; S.Rajathi; S.Ushakumary; Geetha Ramesh; Thokchom S. Sitrajith; Kumar K; K.P. Sharon (Indian Journal of Veterinary Anatomy, 2024)
The objective of this present study was to elucidate the detailed histological features in different segments of oesophagus in adult guinea pigs. Segments of the oesophagus such as cervical, thoracic and abdominal were used. The three segments of the oesophagus were subjected to tissue processing and sections were stained by the routine and special staining techniques. Histologically the oesophagus was lined by four tunics viz., tunica mucosa, submucosa, muscularis and adventitia. The mucosa of the oesophagus of the guinea pigs was lined by stratified squamous keratinized epithelium and there were no glands in the lamina propria and the submucosa. The muscularis mucosa was lined by the smooth muscle cells disposed longitudinally. The tunica muscularis layer was formed by striated muscle cells disposed on 03 layers in the first two thirds length of oesophagus. But in some regions of the abdominal segments of the oesophagus showed four layers of muscles.